Taxonomy of Lecythis Loefl. (Lecythidaceae Poit.) of the Lower Amazon Mesoregion in the State of Pará, Brazil - Sobral, Sofia França; Sousa, Julio dos Santos de; Bastos, Maria de Nazaré do Carmo; Reis, Agirlayne de Souza (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
Taxonomic treatment of Lecythis from Lower Amazon Mesoregion, Pará State, Brazil is provided. The methodology includes the analysis of specimens of the herbaria Museum Goeldi (MG), Agronomic Institute of the North (IAN), National Institute of Research of the Amazon (INPA) and Rio de Janeiro Botanic Garden (RB). The genus is represented by eight taxa: L. alutacea (A. C. Sm.) S. A. Mori, L. corrugata Poit. subsp. corrugata, L. lurida (Miers) S. A. Mori, L. retusa Spruce ex O. Berg, L. pisonis Cambess, L. poiteaui O. Berg, L. prancei S. A. Mori e L. serrata S. A. Mori. These, L. retusa, L. prancei, L. lurida e L. serrata are endemic to Brazil, with L. retusa and L. prancei new records for Pará state.